Visomotor development and use of electronic games in elementary school children - Lima, Thatiana Helena de (2010)
This study investigates the relationships between the perceptual-motor maturity and the use of electronic games, as well the differences between gender and age. 148 children of elementary school participated, of a public institution from Brazil, with 54.1% males and 45.9% female. Students were attending the 2nd to 4th grade. The tests were applied in a collective way, the Bender Test (B-SPG) and a questionnaire to assess the standards of use of electronic games. The results indicated that boys spent more time on electronic games. There was significant correlation between the use of games and the scores of Bender, indicating that children who played more could have more visomotor difficulties. To Bender test no significant differences were found for sex, but to age there have been advances lower was the score.